Association of aromatase (TTTA)n repeat polymorphisms with central precocious puberty in girls. (19th March 2014) - Lee, Hae Sang; Kim, Kyung Hee; Hwang, Jin Soon
Abstract Objective Precocious puberty is characterized by early activation of the pituitary‐gonadal axis. Oestrogen is the final key factor to start the onset of puberty. The cytochrome P450 19A1 (CYP19A1) gene encodes an aromatase that is responsible for the conversion of androgens to oestrogen, which is a key step in oestrogen biosynthesis. The aim of this study was to identify CYP19A1 gene mutations or polymorphisms in girls with central precocious puberty (CPP). Methods We evaluated the frequency of allelic variants of the CYP19A1 exons and the tetranucleotide tandem repeat (TTTA)n in intron 4 in 203 idiopathic central precocious puberty (CPP) girls and 101 normal healthy women. Results The genotype analysis of the CYP19A1 (TTTA)n polymorphism revealed six different alleles ranging from seven to 13 repeats. Among the six different repeat alleles detected in this study, the (TTTA)13 repeat allele was only detected in the patient group and carriers of the (TTTA)13 allele were significantly associated with an increased risk of CPP (OR = 1·509, 95% CI = 1·425–1·598, P = 0·033). Carriers of the (TTTA)13 repeat allele were significantly younger at pubertal onset and had higher levels of oestrogen than noncarriers of the (TTTA)13 repeat allele. Although nine polymorphisms were detected in exons of the CYP19A1 gene, no clinical significance was observed. Conclusion In this study, carriers of a higher repeat (TTTA)13 polymorphism in intron 4 of the CYP19A1 gene had higher levels of oestrogen. Those carrying the (TTTA)13 repeat allele may have a higher risk of developing CPP.